Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan dan Risiko Bisnis Terhadap Struktur Modal - Willy Nurhayadi; Indra Sulistiana; Syifa Nurkhalishah; Anis Fuad Salam; Abdurrohman Abdurrohman (Tirtayasa Ekonomika, 2021)
This research was conducted to determine the effect of company size, sales growth, and business risk on property and real estate companies listed on the Indonesia stock exchange for the 2014-2018 period. This research method uses an associative method with a quantitative approach and data collection techniques using secondary data. The sampling technique used purposive sampling technique, the sample used was 21 companies sourced from the annual financial statements of Property and Real Estate companies on the Indonesia Stock Exchange (IDX).The analysis technique used is statistical test with multiple linear regression method. The results of this study indicate that company size has a significant positive effect on capital structure, sales growth has a significant positive effect on capital structure, and business risk has a significant negative effect on capital structure. As well as simultaneously company size, sales growth, and business risk affect the capital structure.